Inductively coupled in-circuit impedance measurement based on two-port network characterization - Li, Kangrong (2017)
In-circuit impedance information is one of the parameters for condition monitoring of an electrical system. Besides condition monitoring, it also provides impedance information of a switching converter connected to high voltage power supply so that an optimal electromagnetic interference (EMI) filter can be designed for electromagnetic compatibility (EMC) compliance. Thus, an accurate in-circuit impedance measurement system without interrupting the normal operation of an electrical system under test is very useful for the applications mentioned earlier. Existing in-circuit impedance measurement approaches, such as transformer ratio-arm bridge, current sensing and the inductive coupling have been reviewed. The two-probe inductive coupling approach is found to be superior to other approaches, as the measurement setup does not have direct electrical contact to the electrical system being measured and it can be easily mounted on-site for any high-voltage electrical system under its normal condition without electrical safety hazard to the measurement personnel. However, the existing implementation of the two-probe inductive coupling approach has several shortcomings. To overcome these shortcomings, two-port network characterization technique is adopted so that the measurement system setup can be treated as cascaded two-port ABCD networks. With the accurate characterization of the inductive coupling probes, as well as the measurement setup, the setup calibration can be greatly simplified without interrupting the operation of the electrical system under test. In addition, it also enhances the measurement accuracy of the in-circuit impedance.